PENYELESAIAN PEMBIAYAAN MURABAHAH YANG BERMASALAH DI BMT NURUL BAROKAH - Syahida, Nafilah Amalia; Imanullah, Moch. Najib; Mulyanto, , (Fakultas Hukum Universitas Sebelas Maret, 2025)
As a predominantly Muslim country, Indonesia has bothconventional and Islamic financial institutions. Murabahah was themost commonly requested financing by customers to fulfill needsand provide capital goods. However, with its high demand, variousissues often arose in murabahah financing due to multiple factors.This research employed an empirical and descriptive-analyticalmethod, utilizing both primary and secondary data. The factorscausing problematic murabahah contracts at BMT Nurul Barokahwere due to internal and external issues of the customers or theinstitution. To address these problematic financings, BMTNurul Barokah employed various efforts, including litigation, non-litigation, and collateral auction, with different approachesdepending on the customer's condition at the time.